SISTEM INFORMASI KLINIK GIGI OMMI BERBASIS WEB OMMI DENTAL CLINIC INFORMATION SYSTEM WEB-BASED - , SALIS ROSYIDA I ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Ommi Dental Clinic is a clinic that specializes in dental health services. In running programs, that include patient registration process and data management in Ommi Dental Clinic is still using the manual system, it is not web-based, so it can result in a variety of clinical data records lost or damaged because as noted in the paper only. Data management system that is still done manually, require considerable time and inaccurate, so there are some income or expense that has not been recorded. Accoding to the issues, it is necessary to build a system that capable to handle data management and variety of other processes it so the clinicâs service could become more optimal and capable of presenting output, either in the form of information and reports accurately and easily. Ommi Dental Clinic Information System was built using codeigniter framework, the programming language PHP and MySQL database. This information system handles data processing in the form of patient data, data examination or medical record, action data, drug data, payment data and preparing reports in the form of tables and graphs. In addition, the system has an online registration facility. It is expected this information system able to provide convenience to the clinic in data management and able to improve the performance and service towards the patients so that it can be more effective and efficient.